2003
DOI: 10.1074/jbc.m303153200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements for Expression of Factor Va Activity

Abstract: Thrombin activated factor Va (factor V IIa , residues 1-709 and 1546 -2196) has an apparent dissociation constant (K d,app ) for factor Xa within prothrombinase of ϳ0.5 nM. A protease (NN) purified from the venom of the snake Naja nigricollis nigricollis, cleaves human factor V at Asp 697 , Asp 1509 , and Asp 1514 to produce a molecule (factor V NN ) that is composed of a M r 100,000 heavy chain (amino acid residues 1-696) and a M r 80,000 light chain (amino acid residues 1509/1514 -2196). Factor V NN , has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
64
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 81 publications
13
64
2
Order By: Relevance
“…Molecules-Cofactor activity of wild type and mutant molecules was measured in a clotting assay using factor V-deficient plasma prior and after activation by thrombin (15 min, 37°C) and RVV-V activator (2 h, 37°C) as described (43,46). The values were standardized to the percentage of control (55).…”
Section: Determination Of Factor V/va Clotting Activity Of the Recombmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecules-Cofactor activity of wild type and mutant molecules was measured in a clotting assay using factor V-deficient plasma prior and after activation by thrombin (15 min, 37°C) and RVV-V activator (2 h, 37°C) as described (43,46). The values were standardized to the percentage of control (55).…”
Section: Determination Of Factor V/va Clotting Activity Of the Recombmentioning
confidence: 99%
“…This amino acid region, which is highly acidic in nature and contains the tyrosine residues that were previously shown to have the potential to be involved in both procofactor activation by thrombin as well as cofactor function (47,48), may possess residues that are directly involved in the interaction of the cofactor with positively charged amino acids provided by one of the protein components of prothrombinase. Further, we have recently demonstrated that a binding site for prothrombin is located on the last 13 amino acids of the factor Va heavy chain (46). The present study was undertaken to identify the specific amino acid residues from the acidic COOH-terminal region of factor Va heavy chain that are important for cofactor function and the molecular mechanisms underlying their contribution to prothrombinase function.…”
mentioning
confidence: 96%
“…Broadly, these studies found that variable amounts of cofactor activity are observed depending on which region of the B-domain is cleaved and which assay is used to evaluate activity. A clear consensus is that maximal activity correlates with cleavage at Arg 1545 (7,13,(15)(16)(17)(18)(19)(20)(21)(22). Although these studies have advanced the field, such correlative studies have not provided mechanistic insight into how FV activation unfolds.…”
mentioning
confidence: 99%
“…It also enhances the turnover number for prothrombin activation by a factor of about 3000 (7,8). Several groups have shown that factor Va interacts with factor Xa (13,(15)(16)(17). Interactions between factor Va and prothrombin have also been characterized (17)(18)(19)(20).…”
mentioning
confidence: 99%